1996
DOI: 10.1021/jp9521565
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Aqueous Nucleobases, Nucleosides, and Nucleotides on Compost-Derived Humic Acid. 1. Naturally Occurring Pyrimidines

Abstract: Adsorption of the naturally occurring pyrimidine nucleobases and their corresponding nucleosides and nucleotides on compost-derived humic acid (HA) has been studied in aqueous solution. All these nine solutes interact with HA. Adsorption isotherms were measured at 19 solute concentrations from 12-600 µM and 6 temperatures in the range 10.0-40.0°C. Analysis with the Langmuir model indicates that adsorption occurs in three detectable steps A, B, and C, depending on the solute and the experimental conditions. Mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
92
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(98 citation statements)
references
References 21 publications
6
92
0
Order By: Relevance
“…Spectrometry. UV−visible and FTIR spectrometry was conducted with previously described instruments and procedures. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectrometry. UV−visible and FTIR spectrometry was conducted with previously described instruments and procedures. , …”
Section: Methodsmentioning
confidence: 99%
“…This paper reports data for adsorption of uracil, uridine, and uridine-5‘-monophosphate on a humic acid isolated from German peat (GHA) and its tightly bound mercury(II) form (MGHA). The solutes were chosen because they all have the uracil nucleobase unit and CHA has unusually low capacity for uridine . This solute choice is important because other NACs such as adenine have the ability to free up (“create”) more sites after primary adsorption .…”
Section: Introductionmentioning
confidence: 99%
“…Marschner & Bredow () and Khairy et al . (,b) have both observed that a rise in temperature moves the system toward a higher share of non‐sorbed reactants, and temperature has a progressively larger effect as more energy is needed to desorb reaction partners. Temperature also increases diffusion and dissolution, both of which increase substrate availability to soil microbes and leaching losses of soil carbon (Xu & Saiers, ).…”
Section: A Way Forward Through a New Conceptual Frameworkmentioning
confidence: 99%
“…23 for adsorption of 14 nucleic acid constituents (NACs) on a solid compost-derived HA and on solid HA particles from different soil sources without or with added Hg II 24 show that HAs can be purified to the point where they become understandable. The data fit the Langmuir model for reversible solute adsorption in sequential steps labelled i = A, B and C. 14,[22][23][24] Analysis gives the stoichiometric site capacity ν i and the equilibrium constant K i for each solute and step. The ν i data indicate interaction of the HA surface with the nucleobase units of NAC solutes.…”
mentioning
confidence: 89%